Aspectos sedimentológicos y estratigráficos de los depósitos cuaternarios de la costa platense del Departamento de Canelones (Uruguay) Sedimentologic and stratigraphic aspects of the Quaternary deposits along the Plata Coast on the Departamento de Canelones (Uruguay) - César Goso Aguilar (Latin American Journal of Sedimentology and Basin Analysis, 2006)
Esta contribución brinda elementos sedimentológico-estratigráficos de los depósitos cuaternarios que aparecen en los acantilados y plataformas en la costa rioplatense del Departamento de Canelones, Uruguay. Se constató la presencia de depósitos regresivos e ingresivos cuaternarios, materializados por los sedimentos pleistocénicos transicionales de la Formación Chuy y los continentales de las formaciones Libertad y Dolores, así como los transicionales holocénicos de la Formación Villa Soriano. Se caracteriza litológicamente cada unidad, se interpretan los procesos actuantes y se hacen inferencias acerca de los ambientes de sedimentación involucrados. The Uruguayan Quaternary record has been studied by several authors in the last four decades. The Quaternary glacial and interglacial record shows a few tens meters of thickness and is integrated by both sediments and non-depositional surfaces. The sedimentary package is better exposed in the southern region and coastal area of Uruguay. The non-depositional surfaces (iron crust) and paleosoils are better exposed in the north and eastern region. The Lithostratigraphic column proposed by Goso (1965, 1972) focuses the Quaternary record with a precursor genetic point of view, integrating lithologic, geomorphologic and climate conditions. However, this stratigraphic proposal was partially adopted and understood by some scientists. Transitional sediments of the Pleistocene Chuy Formation and continental deposits of Libertad and Dolores formations are present. Also, transitional Holocene sediments of Villa Soriano Formation were shown and are described (Fig. 1). The goal of this paper is to contribute to the knowledge of a part of this record especially towards some sedimentologic and stratigraphic features of the Quaternary deposits exposed along Rio de la Plata coast in the Canelones Department, Uruguay (Figure 2). The Chuy Formation is very well exposed in Villa Argentina and Las Vegas - La Floresta beaches. It is integrated mainly by white conglomerates and coarse to fine sandstones with current and wave traction structures and trace fossils. Also contains fossiliferous green clay deposits. It looks with variable thickness since a few meters to twenty five meters (Figs. 3 and 5). It was deposited during an interglacial period in transitional sedimentary environment, predominantly the shoreface portion in a barrier island and lagoon systems, into tidal conditions. The top of this lithofacies sequence shows a thin (few centimetres) iron crust in the area. This non-depositional surface was also observed in others inner Canelones localities (several Santa Lucia river sections). The Libertad and Dolores Formations can be observed in several localities along the studied area. They are composed mainly of brownish fangolites and silt-clay sediments. Massive, parallel lamination, incised lobes and tabular deposition are the main structures and geometries exposed of these units (Figs 4-8). They were deposited during a Pleistocene glacial period with the alternance of semiarid and temperate conditions and materialize a continental sedimentation (gravity flows, reworked eolian deposits). These units show a few meters of thickness. The Villa Soriano Formation is present in La Floresta beach, Sarandí creek mouth, and is composed mainly by grey fangolites and black fossiliferous clays containing molluscs valves (Figs 3e and 9). This unit was deposited during the current interglacial period and materializes the last ingressive sea-level conditions. Considering both the coastal outcrops and subsurface distribution in Uruguay the Villa Soriano Formation represents the last holocenic embayments and shorelines. The thickness of this unit in the area is less than six meters. The coast of Canelones Department along Río de la Plata shows several meters of quaternary sequences in many locations. In these combined sections two transgressive-regressive cycles were observed and analyzed. The former is composed by sediments of the Libertad II (continental) and Chuy III (transitional) Formations deposited since Medium to Upper Pleistocene, while the latter is constituted by a few meters thickness of sediments that belongs to both Dolores (continental) and Villa Soriano (transitional) formations during the time interval Upper Pleistocene - Holocene.